Microstructure and Magnetic Properties of Electrodeposited Fe-Based Thin Films on Silicon Substrate Under Heat Treatment. Issue 1 (2nd January 2016) - Hou, Xiaowei; Liu, Shibin; Li, Juping; Yang, Shanglin; Guo, Bo
Abstract : Three kinds of Fe-based thin films, Fe–20%Ni–80%, Fe–60%Co–40%, and Fe–10%Ni–60%Co–30% (at %), were prepared on silicon (1 1 1) substrates by direct current electrodeposition with the optimized plating conditions. Films were annealed at various temperatures from 200 to 400 °C, varying time from 2 to 4 h. The microstructure, surface morphology, and chemical composition have been investigated by X-ray diffraction, scanning electron microscopy, energy dispersive spectrometer with electron probe micro-analysis, respectively. The magnetic properties were measured by the superconducting quantum interference device magnetometer. Effect of heat treatment on films is then discussed.